(untitled) (Marketing Journal, 2026)
Abstract This article examines the formation of the logistics services market within the transport system, its historical stages, and current development trends. The role of transport and logistics activities in the economy is analyzed, including the integration of freight and passenger transportation and the development of multimodal transport systems. Special attention is given to the evolution of logistics intermediaries, freight forwarding services, and the impact of digitalization on market efficiency. The study also highlights the modernization of Uzbekistan’s transport system, the development of logistics centers, and improvements in service quality. The findings contribute to strengthening the competitiveness of the national transport system and enhancing the efficiency of the logistics services market. Keywords: cargo delivery system, transport services market, cargo turnover, passenger turnover, transport integration, cargo transportation process, high-tech vehicles, transport systems of countries, international relations.